VD_FINDINFO Décision / 2015 / 696 vom 14. September 2015 - VD Tribunal cantonal (2015)
PLAIGNANT, PERSONNE PROCHE, VICTIME, ACTE D'ORDRE SEXUEL, REPRÉSENTATION LÉGALE | 306 al. 3 CC, 116 CPP (CH), 117 CPP (CH), 382 al. 1 CPP (CH)